Impact of Pharmacists' Religious and Personal Beliefs in Dispensing Contraceptives - Anna Krupa; Albert I Wertheimer (University of Minnesota Libraries Publishing, 2016)
Background: Until recently, pharmacies were not permitted to dispense any emergency contraceptives to women to prevent pregnancy. No legal statutes existed under which pharmacists with religious, moral or ethical objections could refuse to fill a prescription for contraceptives, nor were there direct guidelines describing the pharmacist's professional obligations. Objectives: The purpose of this study is to explore the frequency of cases in which pharmacists have refused, due to their personal beliefs, to provide counsel regarding contraceptives or have refused to refer to a patient to a different pharmacist or healthcare provider. This study will compare and contrast the differences between independent pharmacies and chain pharmacies (i.e. time spent, location, most common recommended contraception). Finally, this study will compare the results evident between male pharmacists and female pharmacists. Method: Quantitative method employed uses two interview questions directed to pharmacists: (1) "I am moving in with my fiancée/boyfriend next month and I have never used contraceptives. What are my options?" (2) "If I use a condom and it breaks, do I have any choices to prevent pregnancy after the fact?" The survey was conducted in two locations, the greater Philadelphia area and Hershey, PA. The survey was conducted through face-to-face interactions with pharmacists, either employed at independent pharmacy or at a chain pharmacy. Data collected from each pharmacist included number of approximate age/gender; minutes spent in each consultation with a patient; the kind of privacy provided during the consultation; and the referrals given, if any. Results: Fifty (50) pharmacists were interviewed. No pharmacist indicated that counseling would be denied, although one (1) pharmacist refused to counsel on Plan B and four (4) pharmacists referred the interviewer to a doctor immediately, indicating that all medications require a prescription. Two (2) pharmacists spent more than 10 minutes providing the best possible counseling.   Type: Student Project